Prospective of climate change impact on water resources and sugar beet yield in the Urmia Lake basin - Somayeh Naderi; Bohloul Alijani; Zahra Hedjazizadeh; Hasan Heidari; Karim Abbaspour (تحقیقات کاربردی علوم جغرافیایی)
Evidence suggests that climate change will create uncertain regional agricultural production stability in the coming decades. This research investigated the impact of climate change on hydrology and sugar beet yield as one of the main crops in the Urmia lake basin using the Soil and Water Assessment Tool (SWAT). To address this, a baseline SWAT model was setup for 1986-2014. Afterward, the output was calibrated (1989-2004) and validated (2005-2014) in the SWAT-CUP software using the SUFI2 algorithm to simulate streamflow of 23 gauging stations and crop yield. The Nash-Sutcliffe efficiency was 0.43 and 0.53 for calibration and validation periods, sequentially. The Percent Bias was 45% and 16% for calibration and validation periods, respectively. As well as the agreement indices of 0.71 and the little Percent Bias (-6% to 10%) for crop production, verified the model's efficiency. The next step was downscaling and bias-correction of the precipitation and temperature data received from 3 climate models, namely GFDL, HadGEM2, and IPSL under RCP4.5 and RCP8.5 using CCT program. Then, the downscaled data were fed to SWAT, and Finally, hydrological fluxes and sugar beet yield were estimated for 2021-2050. Despite a dispersion of precipitation changes ranging from -12% to +35% in most scenarios, results highlight the pivotal role that the warmer temperature (+2.7°C) increases evaporation, resulting in sharpened pressure on water resources and runoff, especially, at the beginning of crop growth season. Finally, the negative impacts on crop productivity (-45%) is not unexpected. This means that sugar beet may suffer from climate change impacts, and the production of this plant will change over the next period in this region.